Determination of best-fit distribution and rainfall events in Damansara and Kelantan, Malaysia - Ho, Ming Kang (2013)
This paper presents a study to determine the best-f it distribution to represent the rainfall process in Damansara and Kelantan, Malaysi a. Three probability density functions, namely Wakeby distribution, Generalized Extreme Val ue function (GEV) and two-parameter Weibull distributions are selected and compared. Th e parameters of the distributions are estimated using L-moments method while the best-fit distribution is determined by using Kolmogorov-Smirnov goodness-of-fit test. In additio n, weighted-average algorithm which is based on the probability values from the stations i n Damansara and Kelantan is used to identify the occurrence of wet and dry events in th e rainfall data. The impact of different distributions used in the determination of rainfall events is evaluated by making comparison between the actual and the reconstructed rainfall d ata. The results indicate that the Wakeby distribution is the best-fit distribution to explai n the rainfall patterns in Damansara and Kelantan. However, Wakeby, GEV and Weibull distribu tions perform equally well in the estimation of wet and dry events in Damansara and Kelantan.